1984
DOI: 10.1007/bf00670538
|View full text |Cite
|
Sign up to set email alerts
|

Afferent C-fibres in rats after neonatal capsaicin treatment

Abstract: Excitability of afferent C-fibres in a skin nerve was studied in 28 rats treated with capsaicin on day two of their lives (80 mg/kg, s.c.). At the age of 4-5 months they were subjected to experiments in which recordings were made from single C-fibre units of saphenous nerve. The effectivity of neonatal capsaicin treatment in blocking reactions to the irritating action of the toxin was evaluated with the wiping test. Five untreated rats served as controls. In capsaicin treated animals afferent cutaneous C-fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Because these changes occur when the percentage of menthol-sensitive neurons is relatively stable, it is plausible that this effect is caused by a specification of existing cells, losing the sensitivity to capsaicin, rather than a loss of the actual cells along with an induction of menthol sensitivity in a new set of cells. This hypothesis is supported by the finding that the severe loss of small-diameter sensory neurons with systemic neonatal capsaicin treatment also produces an equal reduction in heat-sensitive nociceptors and cold-sensitive (and menthol-sensitive) thermoreceptors (Welk et al, 1984). A similar finding was also seen in the development of mustard oil responsiveness, which was widely overlapping in the first two postnatal weeks.…”
Section: Lineage Relationshipsmentioning
confidence: 64%
“…Because these changes occur when the percentage of menthol-sensitive neurons is relatively stable, it is plausible that this effect is caused by a specification of existing cells, losing the sensitivity to capsaicin, rather than a loss of the actual cells along with an induction of menthol sensitivity in a new set of cells. This hypothesis is supported by the finding that the severe loss of small-diameter sensory neurons with systemic neonatal capsaicin treatment also produces an equal reduction in heat-sensitive nociceptors and cold-sensitive (and menthol-sensitive) thermoreceptors (Welk et al, 1984). A similar finding was also seen in the development of mustard oil responsiveness, which was widely overlapping in the first two postnatal weeks.…”
Section: Lineage Relationshipsmentioning
confidence: 64%
“…On the other hand, in the immature nervous system of neonatal rats parenteral capsaicin has a broader target, and less specific destruction of afferent Cand A&-fibre neurones occurs Lynn et al 1984;Welk et al 1984). …”
Section: Capsaicin Desensitizationmentioning
confidence: 99%
“…However, the reports of the reactions of such desensitized animals to noxious mechanical and thermal stimuli have not been consistent, particularly in the case of rats pre-treated neonatally (for reference see Szolcsanyi, 1982Szolcsanyi, , 1985Nagy, 1982;Fitzgerald, 1983;Russell & Burchiel, 1984). Recent single-unit studies have shown that long-term functional impairment after applying capsaicin to axons occurs only for polymodal nociceptors, while systemic pre-treatment of neonatal rats results in an indiscriminate loss of afferent C fibres (Lynn, Carpenter & Pini, 1984;Handwerker, Holzer-Petsche, Heym & Welk, 1984;Welk, Fleischer, Petsche & Handwerker, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity to capsaicin in each animal belonging to either the capsaicin- or vehicle-treated group was evaluated by observing the behavioral responses to instillation of capsaicin solution to the cornea according to a previously described method ("eye-wiping test" in [53,54]). The 0.01% capsaicin eye instillation solution was made by diluting the stock solution containing 1% capsaicin, 10% ethanol and 10% Tween-80 with saline to 1:100.…”
Section: Methodsmentioning
confidence: 99%